PENERAPAN MODEL PEMBELAJARAN TANDUR UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SDN TANJUNG DUREN UTARA 02 PAGI - Mawarni; Harlinda Syofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning outcomes of fourth-grade students at SDN Tanjung Duren Utara 02 Pagi Jakarta through the implementation of the TANDUR learning model in IPAS instruction. The research involved 16 fourth-grade students and was conducted during Cycle I of the Classroom Action Research. The method employed was the Classroom Action Research (CAR) model developed by Kemmis and McTaggart, consisting of the planning, action, observation, and reflection stages. The data analysis technique used was descriptive quantitative analysis. Based on the implementation of the TANDUR model, the students’ average learning activity reached 100%, and the percentage of learning mastery achieved 100%. All students obtained scores above the Learning Objectives Achievement Criteria (KKTP). The findings indicate that students became more active, motivated, and demonstrated better understanding of IPAS materials. Thus, the TANDUR learning model is effective in significantly improving students’ learning outcomes.